The Role of Radio in Promoting the Folk and Sufiana Music in the Kashmir Valley: Exploring the Impact of Radio on Kashmiri Folk and Sufiana Music (Journal of Advances and Scholarly Researches in Allied Education, 2016)
In this Research work the Researcher reveals the role of All India Radio Srinagar in promoting the folk and sufiana music of Kashmir. Sufiana music is also known as the classical music of Kashmir. There was a time when the radio was considered to be a kind of entertainment only. At that sphere of time, All India Radio Kashmir was also touching the sky from its potential. Radio was widely heard among masses. Radio plays a significant role in the promoting of kashmiri music and the musicians of Kashmir. In this research work the researcher has written about role of Radio in Kashmiri music and in the success of kashmiri musicians.